Genome-Wide Association Study and Genomic Prediction for Bacterial Wilt Resistance in Common Bean (Phaseolus vulgaris) Core Collection - Zia, Bazgha; Shi, Ainong; Olaoye, Dotun; Xiong, Haizheng; Ravelombola, Waltram; Gepts, Paul; Schwartz, Howard F.; Brick, Mark A.; Otto, Kristen; Ogg, Barry; Chen, Senyu (Frontiers in Genetics, 2022)
Common bean (Phaseolus vulgaris) is one of the major legume crops cultivated worldwide. Bacterial wilt (BW) of common bean (Curtobacterium flaccumfaciens pv. flaccumfaciens), being a seed borne disease, has been a challenge in the common bean producing regions. Genome-wide association study (GWAS) was conducted to identify SNP markers associated with bacterial wilt (BW) resistance in the USDA common bean core collection. A total of 168 accessions were evaluated for resistance to three different isolates of bacterial wilt (BW). Our study identified a total of 14 single nucleotide polymorphisms (SNPs) associated with interactions with bacterial wilt (BW) isolates 528, 557, and 597, using the mixed linear models (MLM) in BLINK, FarmCPU, GAPIT and TASSEL 5. These SNPs were located on chromosomes Phaseolus vulgaris [Pv]02, Pv04, Pv08, and Pv09 for isolate 528; chromosomes Pv07, Pv10, and Pv11 for isolate 557; and chromosomes Pv04, Pv08, and Pv10 for isolate 597. The genomic prediction accuracy was assessed by utilizing seven GP models with 1) all the 4,568 SNPs; and 2) the 14 SNP markers. The overall prediction accuracy (PA) ranged from 0.30 to 0.56 for resistance to the three bacterial wilt (BW) isolates. A total of 14 candidate genes were discovered for bacterial wilt (BW) resistance located on chromosomes Pv02, Pv04, Pv07, Pv08, and Pv09. This study revealed vital information for developing genetic resistance against the bacterial wilt (BW) pathogen in common bean. Accordingly, the identified SNPs and candidate genes can be utilized in common bean molecular breeding programs to develop novel resistant cultivars.